Did social isolation affect anxiety and sleep quality of elite soccer players during the COVID-19 lockdown? Comparisons to training before distancing in the pandemic and outlook for mental health - da Cruz, Whyllerton Mayron; Coimbra, Danilo Reis; Vilarino, Guilherme Torres; dos Santos, Amândio Manuel Cupido; da Silva, Vernon Furtado; Mancone, Stefania; Falese, Lavinia; Diotaiuti, Pierluigi; Andrade, Alexandro (Frontiers in Psychology, 2024)
To analyze the anxiety levels and sleep quality of elite soccer athletes in training pre-pandemic and during the lockdown caused by COVID-19. Method: This is an exploratory study with a longitudinal design carried out with elite soccer athletes from two Brazilian soccer clubs. Data collection took place in person pre-pandemic (training) and online (during lockdown) between February and May 2020. The instruments used to assess sleep, daytime sleepiness, and anxiety were the Pittsburgh Sleep Quality Index (PSQI), Epworth Daytime Sleepiness Scale -(ESS-BR), and Competitive Anxiety Scale (SCAT). For data analysis, descriptive statistics (frequencies, percentages, maximum and minimum) and non-parametric inferential statistics were used, establishing a significance of p<0.05. Results: In total, 76 male soccer athletes participated in the study. A significant increase was observed in anxiety levels in confinement compared to prepandemic training (p=0.017; g=0.83), and sleepiness significantly reduced in training compared to baseline levels (p=0.007 g=0.48). The athletes demonstrated good sleep quality and the pandemic did not significantly alter daytime sleepiness compared to training and baseline. Conclusion: From the results it can be concluded that elite soccer athletes presented alterations in anxiety levels compared to training during confinement, however, no effects of confinement were observed on sleep quality and sleepiness. New studies are needed to analyze the long-term consequences of the pandemic and the relationships between anxiety and sleep in training and competition in athletes.